The Effect of Eco-Friendly Packaging on Purchase Intention with Consumer Perception as an Intervening Variable - Esvandiari, Megia; Susan, Marcellia; Mulyaningsih, Hendrati Dwi; Muhardi; Oktini, Dede R; Nurhayati, Nunung (International Journal of Entrepreneurship and Sustainability Studies, 2023)
The increasing use of plastic water bottles has exacerbated the global plastic waste crisis. Eco-friendly packaging is the concept of reducing and recycling plastic packaging waste. AQUA carried out this concept with Danone, who launched the AQUA Life product. This study aimed to determine the direct and indirect effects of eco-friendly packaging on the purchase intention of AQUA Life products through consumer perception and to analyze descriptively how eco-friendly packaging, consumer perception, and purchase intention of AQUA Life products. The analysis technique in this study uses Path Analysis to determine the role of consumer perception in mediating eco-friendly packaging on the purchase intention of AQUA Life products. The results showed that descriptive analysis for eco-friendly packaging, consumer perception, and purchase intention for AQUA Life products received good responses. \]And it was found that the magnitude of the indirect effect of eco-friendly packaging on purchase intention was more significant than the direct effect. This means that consumer perception as an intervening variable significantly influences eco-friendly packaging on purchase intention. The research results are expected to help the company add other features, such as the reuse idea for consumers, and reconsider product selling prices. To directly increase purchase intention, the company should pay attention to factors that influence consumer purchasing intentions, such as increasing the popularity of products.